Third Generation Human Rights and their constitutional incidence in Ecuador - Cisneros Salcedo, Caetano Galicio (2023)
Ecuador owns vast constitutional history, although there are several constitutional texts, however, it is hardly possible to speak of two conjunctural breaks on the constitutional history. Following this line, it is necessary to approach to the third-generation human rights and their constitutional incidence in the current constitution of Ecuador. There are specific issues related to first- and second-generation rights, however, it is necessary to carry out an analysis of human rights considered to be of the third generation, since many of the fundamental rights head the process of fundamental principles and guarantees.